2016
DOI: 10.5194/amt-9-3619-2016
|View full text |Cite
|
Sign up to set email alerts
|

A multi-wavelength classification method for polar stratospheric cloud types using infrared limb spectra

Abstract: Abstract. The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) instrument on board the ESA Envisat satellite operated from July 2002 until April 2012. The infrared limb emission measurements represent a unique dataset of daytime and night-time observations of polar stratospheric clouds (PSCs) up to both poles. Cloud detection sensitivity is comparable to space-borne lidars, and it is possible to classify different cloud types from the spectral measurements in different atmospheric windows regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 66 publications
(106 reference statements)
2
71
0
Order By: Relevance
“…The detection and classification results were compared with space-borne lidar observations. Spang et al (2016) showed that ice particles are classified most accurately with the new method. Our survey of gravity-wave-induced PSC formation events is based on daily maps of detrended and noise-corrected AIRS 15 µm brightness temperature variances and MIPAS PSC detections.…”
Section: A Survey Of Gravity-wave-induced Psc Formation Eventsmentioning
confidence: 98%
See 2 more Smart Citations
“…The detection and classification results were compared with space-borne lidar observations. Spang et al (2016) showed that ice particles are classified most accurately with the new method. Our survey of gravity-wave-induced PSC formation events is based on daily maps of detrended and noise-corrected AIRS 15 µm brightness temperature variances and MIPAS PSC detections.…”
Section: A Survey Of Gravity-wave-induced Psc Formation Eventsmentioning
confidence: 98%
“…A particular advantage of MIPAS was its sensitivity to low particle concentrations due to the long integration paths of the limb observation geometry. Here, we make use of a new MIPAS PSC data product introduced by Spang et al (2016), which uses radiance measurements at 7.1, 8.2, 10.5, 12.0, and 12.7 µm to detect PSCs and to classify different particle types. The new method has been developed and tested with a database of radiative transfer model calculations of realistic PSC particle size distributions, geometries, and composition.…”
Section: A Survey Of Gravity-wave-induced Psc Formation Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…A8b shows that the measurements above the separation lines disappear, except for a few PSC detections south of 60 • N over Siberia and some aerosol in the tropics. The fact that the BTD correlation used here for filtering out ice clouds also improves the discrimination between ice and non-ice PSCs has been investigated in a separate study by Spang et al (2016). …”
Section: A4 Separation Between Ice Clouds and Non-ice Pscsmentioning
confidence: 99%
“…Section 2 introduces MIPAS and other involved instruments. Section 3 provides a summary of the MIPAS detection and classification method -more extensively presented in Spang et al (2016) -is given in conjunction with a comparison to CALIPSO and plausibility tests for the results of the classification approach. Section 4 describes in detail various aspects of the climatology, like temporal and spatial evolution of the PSC type distribution.…”
mentioning
confidence: 99%